Odnos do dela s starostniki med kliničnimi mentorji - Hvalič Touzery, Simona (Obzornik zdravstvene nege, 2013)
Introduction: Demographic changes herald a new challenge to nursing - ensuringan appropriate range of effective and quality nursing care services for older adults. Yet, despite an urgent need for skilled gerontological health professionals, studies show that working with older people is not an attractive career choice. The purpose of this study was to determine the interest in geriatric nursing careers among clinical mentors who had experience in working with old people. Methods: The study was conducted from June to September 2010, on the convenience sample of clinical mentors (n = 128). Questionnaires were distributed among clinical mentors in 17-clinical environments in Slovenia. The questionnaire on nurses' attitudes towards gerontological nursing contained closed format questions. Data was processed with the statistical package SPSS 20.0. The research is based on the non-experimental quantitative method. Results: Age of clinical mentors has statistically significant impact on their attitude to gerontological nursing education (p = 0.002) and their attitude towards old age (p = 0.019) and ageing (p = 0.019). Clinical mentors believe that there should be more hours of gerontological nursing included in curriculum of the future nurses. The interest in gerontological nurising is higher among those who see nursing of old people as challenging (p < 0,001), who have more knowledge on the specifics of gerontological nursing (p = 0.010) and who desire more gerontological knowledge (p < 0.001). Interest in working with old people expressed 73.9% of clinical mentors in the sample. Discussion and conclusion: Research shows positive attitude among the interviewed to age and ageing and emphasizes the need to develop postgraduate knowledge in the field of gerontology. Gerontological education is a very important strategy to improve nurses' attitude towards old people. The clinical mentors with experience with older patients showed a high level of interest in gerontological nursing, which offers support for previous studies. The research shows that clinical mentors hold positive attitude towards old people, which is important as they can encourage nursing students' interest to work in the gerontological nursing.
Keywords: attitudes; clinical mentors; gerontological nursing; klinični mentorji; old people; stališča; stari ljudje; starostniki; zdravstvena nega